The mansions of Lima: a heritage that we must conserve - Rey y Cabieses, Amadeo-Martín (2025)
One of the fundamental heritages of a city, which combines the material and the immaterial at the same time, are its houses, and especially those that we can call historical and unique, where much has been lived and in which the art and sophistication of the architecture are manifested in a more palpable way. The soul of Lima is made up in part of its mansions, stately mansions full of life and stories to tell. This article aims to draw attention to them and induce people to protect them from destruction and conserve them with care, like someone who takes care of the most intimate part of their being.